Una curiosa Malaxis (Orchidaceae) del occidente de México - Gonzalez-Tamayo, Roberto (Instituto de Ecología, A.C., 1994)
Malaxis ramirezii is proposed as a new species to science and is compared to M. martinezii R. González, from which it is distinguished by its oblong-elliptic (not suborbicular ovate) lateral sepals, acute (not obtuse, truncate or emarginate) petals, and more developed uncinate lateral lobes of the lip (not reduced to minute deltoid apicules), among other differences.